Current Australasian practice for diagnosis and management of idiopathic pulmonary fibrosis: Where are we now?. Issue 4 (22nd March 2015) - Troy, Lauren K.; Chapman, Sally A.; Lake, Fiona; Wilsher, Margaret L.; Honeysett, Liarna B.; Macansh, Sacha; Corte, Tamera J.
Abstract Background and objective Recent international consensus statements have refined evidence‐based guidelines for the diagnosis and management of idiopathic pulmonary fibrosis (IPF). This study sought to investigate how closely these guidelines are adhered to and to compare current practices with those of a similar cohort 15 years ago. Methods A questionnaire on IPF diagnosis and management was distributed to respiratory physicians practising in Australia and New Zealand, in 2012–2013, and results were compared with a similar survey conducted in 1999. Results A total of 172 and 144 questionnaires were completed in 1999 and 2012–2013, respectively. The most important investigations in both survey populations were high‐resolution computed tomography scans, spirometry, diffusing capacity for carbon monoxide, chest X‐ray, static lung volumes and autoimmune serology. In 1999, physicians were more likely to perform arterial blood gases, bronchoalveolar lavage and transbronchial lung biopsy. In the 2012–2013 cohort, 6‐min walk tests and pulse oximetry were more widely utilized. Treatment choices differed considerably between the two survey populations. In 1999, the majority would offer a steroid‐based regimen, whereas most would not use any specific treatment or would refer for trial participation in 2012–2013. Conclusions Approach to IPF diagnosis and management is not uniform and has changed over 15 years. Surveyed respiratory physicians were generally practising in accordance with clinical guidelines, although significant variation in practice was identified in both cohorts. This study identifies the need to standardize care of IPF patients across Australia and New Zealand.